Acute effects of cocaine and cannabis on reversal learning as a function of COMT and DRD2 genotype. - Spronk, Desirée; Schaaf, Marieke; Cools, Roshan; Bruijn, Ellen; Franke, Barbara; Wel, Janelle; Ramaekers, Johannes; Verkes, Robbert (Psychopharmacology, 2016)
Rationale: Long-term cannabis and cocaine use has been associated with impairments in reversal learning. However, how acute cannabis and cocaine administration affect reversal learning in humans is not known. Objective: In this study, we aimed to establish the acute effects of administration of cannabis and cocaine on valence-dependent reversal learning as a function of DRD2 Taq1A (rs1800497) and COMT Val108/158Met (rs4680) genotype. Methods: A double-blind placebo-controlled randomized 3-way crossover design was used. Sixty-one regular poly-drug users completed a deterministic reversal learning task under the influence of cocaine, cannabis, and placebo that enabled assessment of both reward- and punishment-based reversal learning. Results: Proportion correct on the reversal learning task was increased by cocaine, but decreased by cannabis. Effects of cocaine depended on the DRD2 genotype, as increases in proportion correct were seen only in the A1 carriers, and not in the A2/A2 homozygotes. COMT genotype did not modulate drug-induced effects on reversal learning. Conclusions: These data indicate that acute administration of cannabis and cocaine has opposite effects on reversal learning. The effects of cocaine, but not cannabis, depend on interindividual genetic differences in the dopamine D2 receptor gene.